Pelatihan Peningkatan Kapasitas UMKM dan Kepariwisataan - Veronica, Veronica; Roozana Maria Ritonga; Wening Ramadhani Siti Nawangwulan (Jurnal Abdimas Perbanas, 2024)
On July 15, 2024, a community service activity was held in Kampung Dadap Timur with the topic "Training for Enhancing the Capacity of MSMEs and Tourism." The primary goal of this activity was to improve the skills and capacity of Micro, Small, and Medium Enterprises (MSMEs) and tourism destination management in the area. Initial observations identified fundamental needs in MSME management, budgeting for traditional food businesses, and applying the Sapta Pesona tourism concept. These findings served as the basis for designing relevant and targeted training materials. Preparations for the activity included intensive coordination among the service team to ensure the readiness of materials and equipment. Preparations also involved selecting and setting up the training venue, including audiovisual facilities and printed materials. The training covered: (1) MSME management strategies, including business planning, marketing, and product development; (2) budgeting techniques for traditional food MSMEs, including cost estimation, financial management, and pricing strategies; (3) application of the Sapta Pesona concept in tourism to enhance the quality of tourist experiences; and (4) practical sessions teaching how to make chicken dumplings and Es Kuwut. The training was designed to provide practical skills and in-depth knowledge to participants. Evaluation of the activity indicated that the training had a significant positive impact. Participants felt more confident and prepared in managing their businesses and tourism. However, the evaluation also identified some challenges, including the need for more specific case studies and ongoing support. It is recommended that future activities include follow-up sessions and more diverse training materials.